2018
DOI: 10.1038/s41598-018-29024-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of nsP2 protease based cell free high throughput screening assay for evaluation of inhibitors against emerging Chikungunya virus

Abstract: Chikungunya virus has emerged as one of the most important global arboviral threats over the last decade. Inspite of large scale morbidity, with long lasting polyarthralgia, so far no licensed vaccine or antiviral is available. CHIKV nsP2 protease is crucial for processing of viral nonstructural polypeptide precursor to release enzymes required for viral replication, thus making it a promising drug target. In this study, high cell density cultivation (HCDC) of Escherichia coli in batch process was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Twelve inhibitors were used to study the inhibition and it was found that the enzyme was completely resistant to the inhibitors of serine proteases (PMSF, AEBSF, aprotinin), aspartic proteases (pepstatin) and metalloproteases (EDTA) while it was moderately inhibited by cysteine protease inhibitor leupeptin, chymostatin and E-64. HEV protease was strongly inhibited by E-64 (99%) and chymostatin (98%), which had been reported to inhibit papain like cysteine protease (Saha et al, 2018). To confirm these results, modeled HEV protease structure has been docked with above inhibitors which shows that cysteine protease inhibitors E64, Chymostatin, Leupeptin, and ALLN have good docking score and strong binding affinity whereas remaining inhibitors PMSF, Phosparamidon, AEBSF, Bestatin and Pepstatin showed no or weak interactions and EDTA and Antipain remain undocked.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve inhibitors were used to study the inhibition and it was found that the enzyme was completely resistant to the inhibitors of serine proteases (PMSF, AEBSF, aprotinin), aspartic proteases (pepstatin) and metalloproteases (EDTA) while it was moderately inhibited by cysteine protease inhibitor leupeptin, chymostatin and E-64. HEV protease was strongly inhibited by E-64 (99%) and chymostatin (98%), which had been reported to inhibit papain like cysteine protease (Saha et al, 2018). To confirm these results, modeled HEV protease structure has been docked with above inhibitors which shows that cysteine protease inhibitors E64, Chymostatin, Leupeptin, and ALLN have good docking score and strong binding affinity whereas remaining inhibitors PMSF, Phosparamidon, AEBSF, Bestatin and Pepstatin showed no or weak interactions and EDTA and Antipain remain undocked.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the best concentration of each inductor, three concentrations were chosen based on previous studies. For IPTG, concentration often ranges from 0.10 mmol L −1 to 1.00 mmol L −1 [ 21 , 22 , 23 , 24 ] while lactose concentration varies from 10 g L −1 to 18 g L −1 [ 25 , 26 , 27 ]. Considering the reported concentrations, IPTG was evaluated at 0.10 mmol L −1 , 0.45 mmol L −1 and 1.00 mmol L −1 and lactose was evaluated at 10 g L −1 , 14 g L −1 and 18 g L −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Various inhibitors such as sinefungin, aurintricarboxylic acid, and ribavirin were assessed and their inhibitory effect against nsP1 was reported. In addition, nsP2 protease-based cell-free high-throughput screening assay for evaluation of inhibitors against emerging CHIKV has been developed (Saha et al, 2018). These successful methods for identifying antiprotease molecules together with a highthroughput screening assay can lead to the development of industrial level largescale screening platform for identification of protease inhibitors against emerging and reemerging viruses.…”
Section: Viral Target Proteins For Drug Developmentmentioning
confidence: 99%